Effects of acute hypoxia tests on blood markers in high-level endurance athletes - Mounier, R.; Pialoux, V.; Schmitt, L.; Richalet, J. P.; Robach, P.; Coudert, J.; Clottes, E.; Fellmann, N. (European Journal of Applied Physiology, 2009)
The aim of this study was to determine the response of blood markers to acute hypoxia in high-level endurance athletes before training based on "living high-training low" model. Thirty endurance athletes performed a hypoxic cycling test and spent 3 h at rest in a simulated altitude of 3,000 m. At the end of the hypoxic cycling test, the quantity of the natural antisense transcript of HIF-1a mRNA (aHIF) transcript increased significantly (+37%, P = 0.024). After 3-h exposure, at a simulated altitude of 3,000 m, the amount of HIF-1a mRNA increased significantly (+57%, P = 0.012). Moreover, a large inter-subject range was observed in response to the hypoxic cycling test and to the prolonged hypoxic exposure: -133%/+79% and -82%/+653% for HIF-1a mRNA, 69%/+324% and -76%/+229% for aHIF. This study shows a large inter-variability of blood markers in elite athletes in response to acute hypoxic exposure corroborating previous observations made in other populations.